Fungal Keratitis Caused By Epicoccum Sorghi - A Case Report - Lakshey Dudeja; Jeganathan Lakshmipriya; R Karpagam; N Venkatesh Prajna; Lalitha Prajna (Delhi Journal of Ophthalmology)
A 40 year old male presented with redness, pain and watering in his right eye since 3 days. He did not give any history of ocular trauma. A slit lamp evaluation showed a corneal ulcer with feathery margins suggestive of fungal keratitis which was confirmed by microscopic evaluation of the corneal smear. The species of the organism could not be identified by conventional phenotypic methods. A subsequent DNA sequencing identified it to be Epicoccum sorghi, a known plant pathogen. The keratitis healed with topical voriconazole (1%) eye drops in about 4 weeks with a residual scar.